Factors Associated with 30-Day Hospital Readmission among Older Adults: A Secondary Data Analysis - Widhowati, Siwi Sri; Yuniarsih, Sri Mumpuni; ‎ , Kusnadi; Nahdliyyah, Ade Irma; Hasanah, Nunung; Efendi, Ferry (KnE Social Sciences, 2024)
Hospital readmissions among older adults pose a significant risk to society. Continued interprofessional efforts are needed to identify older adults at risk for readmission to improve patient health outcomes after hospitalization. This study investigated the factors associated with 30-day hospital readmissions among older adults. Method: This study used secondary data analysis from individual patient electronic health records, covering all the admissions data of older adults within one year ( January 1 – December 31, 2022) at one general hospital in Pekalongan, Central Java, Indonesia. The study comprised a sample of 930 older adult patients, of which 48 (5.2%) experienced 30-day readmissions, while 882 (94.8%) did not. Binary logistic regression was used to test the relationship between independent variables and dependent variable in bivariate and multivariate analysis. Results: The prevalence of 30-day readmission among older adults was 5.2%. More than half of the 30-day readmissions occurred in males, and married older adults. The average length of hospitalization at initial admission was 3.44 + 2.377 days. The top three main medical diagnoses at initial admissions were cataracts (22.9%), cardiovascular diseases (16.7%), and renal diseases (14.6%). Based on multivariate analysis, the factors significantly associated with 30-day readmission were marital status (AOR: 3.161, 95% CI = 1.577 – 6.337) and kidney disease-related diagnosis (AOR: 4.090, 95% CI = 1.664 – 10.052). Conclusion: Kidney diseases may play a crucial role in screening for 30-day readmission risk. The hospital should evaluate the care process of patients with kidney disease, to reduce the number of preventable readmissions. Furthermore, the presence of a primary caregiver for older adults should be part of discharge planning in the hospital. Keywords: elderly, readmission, risk, hospitalization, well-being, diagnoses